Les nouvelles causes du patrimoine. L’exemple du Musée Urbain Tony Garnier à Lyon - Alain Chenevez (EchoGéo)
In this article, it is argued that 'heritage' is a product of history that requires cultural and political recognition if that status is to be attributed. The Etats-Unis neighbourhood of residential blocks was built in suburban Lyon during the 1930s, following the designs of Tony Garnier. The aim was to provide good housing and services for members of the working class, although some professionals also moved in. By the 1960s, many buildings had deteriorated; not until the late 1980s was restoration started. Now, the area forms the 'Tony Garnier Urban Museum', with UNESCO recognition. The transformation from dilapidated housing estate to heritage feature, with remarkable external murals, required complex negotiation between residents, planners, architects and local politicians, often involving significant social contestation.